2003
DOI: 10.1007/s00439-003-1021-6
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the "Silver syndrome locus" on chromosome 11q12-q14 in four families and exclusion of eight candidate genes

Abstract: Silver syndrome is a rare variant of autosomal dominant complicated hereditary spastic paraparesis (HSP), in which spasticity of the lower limbs is accompanied by amyotrophy of the hands and occasionally also the lower limbs. The disease locus has been mapped to chromosome 11q12-q14. We report four Austrian families presenting with the typical clinical features of Silver syndrome. Sixteen individuals were affected upon clinical and/or electrophysiological examination. Ten persons showed mild to severe spastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Our findings may be relevant as well to other complex neurodegenerative processes in which lipofuscin accumulates (36). A number of unexplained adult onset peripheral neuropathies are linked to the region from 11q12 to 11q14 region containing the cat F gene (18,42). However, some of these have recently been shown to be caused by mutations in BSCL2 and are inherited in an autosomal dominant manner (12).…”
Section: Discussionmentioning
confidence: 65%
“…Our findings may be relevant as well to other complex neurodegenerative processes in which lipofuscin accumulates (36). A number of unexplained adult onset peripheral neuropathies are linked to the region from 11q12 to 11q14 region containing the cat F gene (18,42). However, some of these have recently been shown to be caused by mutations in BSCL2 and are inherited in an autosomal dominant manner (12).…”
Section: Discussionmentioning
confidence: 65%
“…A whole-genome scan established linkage to chromosome 11q12-q14, and several candidate genes were excluded by sequence analysis 6 . This chromosomal region overlaps the region involved in Silver syndrome 3 .…”
Section: Distal Hereditary Motor Neuropathy (Dhmn) or Distal Spinal Mmentioning
confidence: 99%
“…To investigate this possibility, we recruited the following additional families: four Austrian families 6 with spastic paraparesis and amyotrophy of the hands (F01-F04), one Italian family with pure motor neuropathy sometimes starting in the hands (F16), seven Austrian families with dHMN-V (F08-F15), one Belgian family with spastic paraparesis and with distal amyotrophy always starting and predominating in the legs (F05), one Brazilian family (F06) and the original English family described by Silver 2 (F07) and one English family (F17) with dHMN-V. Fine mapping indicated that the disease in all families could be linked to SPG17 and reduced the candidate gene interval from 13 cM to 2.5 cM, placing the critical region between the markers D11S1765 and D11S1883 (ref. 6).…”
Section: Distal Hereditary Motor Neuropathy (Dhmn) or Distal Spinal Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathy is a well-recognised association in complicated HSP, but is commonly asymptomatic, usually sensory, and is largely limited to descriptions of axonal degeneration [4,5,10]. Distal sensorimotor neuropathy and mixed demyelinating-axonal changes on neurophysiological studies have been occasionally reported with complicated HSP [11,12].…”
Section: Hereditary Spastic Paraplegiasmentioning
confidence: 99%